Perbandingan Penyuluhan Keselamatan dan Kesehatan Kerja terhadap Kepatuhan Pemakaian Alat Perlindungan Diri (APD) Pekerja - Fauziah Gusvita; Ismail Effendi; Nur Aini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to see the effectiveness of occupational safety and health education on using personal protective equipment at PT. Wijaya Karya Tbk Beton Medan. The method used in this study is an experimental quasi-experimental design with a pre-test and post-test design. The sample in this study was 100 workers at PT. Wijaya Karya Beton. The results showed a significant change in the effectiveness of occupational safety and health education with compliance with the use of PPE. The average value of the first observation is 3.97, the second observation is 5.92 and the third observation is 6.00. In conclusion, the counseling carried out proved effective in increasing compliance with PPE at PT. Wijaya Karya Tbk Beton Medan. Keywords: Compliance with the Use of PPE, Safety and Health, Occupational Safety Counseling